Stepwise conformational cooling towards a single isomeric state in the four internal rotors system 1,2-butanediol - Reva, Igor D. (2006)
The present work explores the possibilities of the matrix isolation technique in the structural characterisation of highly flexible molecules. To date, most studies of this type were carried out on molecules with three or less internal degrees of freedom and a few (less than 10) possible conformations. The molecule of 1,2-butanediol has four conformationally relevant three-fold rotational axes, which can result in 81 possible conformations. A detailed theoretical study, at the MP2 and DFT(B3LYP) levels of theory with the 6-311++G(d,p) basis set, revealed that more than 20 conformers of 1,2-butanediol have relative energies in a 0–10 kJ mol–1 range and contribute appreciably to the gas phase equilibrium at room temperature. This fact renders conformational studies of the system extremely difficult under normal conditions. However, the method of matrix isolation permits the reduction of the number of populated conformational states in the experiment at low temperature due to the effect known as conformational cooling: low energy barriers promote the relaxation of the higher energy local minima into more stable structures. As a result of massive conformational cooling occurring upon matrix deposition, only five conformers of 1,2-butanediol were retained in the samples at 10 K. These conformers were identified using a combination of FTIR spectroscopy and extensive theoretical calculations of vibrational spectra. Annealing of the matrices up to 50 K resulted in the extreme case of conformational cooling related with the depopulation of all conformers into the most stable unique structure. The observed transformations were rationalized in terms of barriers to intramolecular rotation.